Local Governance Challenge in Karachi: A Crisis of Authority and Coordination - Sami, Abdul; Abbas, Mazhar (sourcecoder, 2025)
This research paper examines the structural and political factors contributing to Karachi’s governance issues, primarily stemming from an excessive number of bureaucrats and inadequate coordination. Karachi, the largest city and economic centre of Pakistan, is home to almost 20 million people. The city’s weak infrastructure and poor governance lead to numerous issues. Despite accounting for nearly 25 per cent of the nation’s GDP, the city is poorly managed and has a dysfunctional power structure. Racial politics and continuous power struggles between various political factions within the provincial bureaucracy are the primary reasons why attempts to decentralise government have not resulted in efficient local management. Among the city’s many major problems are insufficient public transit, erratic water supply, garbage collection problems, and unbridled urban expansion. These issues show how urgently improved governance is needed